Steady Aligned MHD free convection of ferrofluids flow over an inclined plate / Mohd Rijal Ilias, Noraihan Afiqah Rawi and Sharidan Shafie - Ilias, Mohd Rijal; Rawi, Noraihan Afiqah; Shafie, Sharidan (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Numerical investigation is carried out for the MHD free convection laminar boundary layer flow that allows heat transfer of an electrically conducting Fe₃O₄–kerosene and Fe₃O₄–water-based ferrofluids. For this, an inclined plate is employed that has aligned magnetic effect as well as transverse magnetic field effect. Suitable similarity transformations are used to convert governing partial differential equations into coupled nonlinear ordinary differential equation. The Keller Box method, a well-known explicit finite difference scheme, is then employed to solve transformed equations numerically. For different values of physical parameters, a detailed parametric study is conducted. Means of graphs are extrapolated to determine the effects of all these parameters over temperature and the flow field. For various values of physical parameters, the numerical values are obtained and tabulated for skin friction coefficient and the rate of heat transfer as well. The results when compared with previously published studies were found to be in excellent agreement.